2002
DOI: 10.1046/j.1463-1318.2002.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the temporary loop ileostomy

Abstract: OBJECTIVE: To evaluate the complications of the temporary loop ileostomy. METHOD: A retrospective study of 222 consecutive patients with low anterior resection, ileal pouch-anal anastomosis or continent ileostomy and a diverting loop ileostomy routinely fashioned during the primary operation. The loop ileostomy was closed in 213 patients (96%) during the minimum follow-up period of 15 months. RESULTS: Four patients (2%) required preterm closure of the ostomy due to stomal retraction (n = 3) or bowel obstructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 10 publications
5
56
0
2
Order By: Relevance
“…The 30-day mortality rate after elective reversal of electively and urgently defunctioned patients was 0.9% (1 of 111), which compares to 0.5% recently described. 16,20 This additional risk of mortality should be included in the total early mortality.…”
Section: Matthiessen Et Almentioning
confidence: 99%
“…The 30-day mortality rate after elective reversal of electively and urgently defunctioned patients was 0.9% (1 of 111), which compares to 0.5% recently described. 16,20 This additional risk of mortality should be included in the total early mortality.…”
Section: Matthiessen Et Almentioning
confidence: 99%
“…However, diverting loop‐ileostomy potentially increases the risks for stoma‐related complications including small bowel obstruction (SBO), stoma prolapse, stoma retraction, parastomal hernia, parastomal dermatitis, and mucocutaneous dehiscence. Risks for stoma‐related complications are reportedly 5‐46% 6, 7, 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…Some surgeons use a protective stoma after LAR to prevent anastomotic leakage in the hope that by diverting the fecal stream and keeping the anastomosis free of material, leakage will be less likely. While other surgeons have reported that covering the protective stoma had no influence on anastomotic leakage and reoperation rates, the further complications that can be caused by the stoma itself should not be ignored, as they include discomfort and inconvenience, high output with consequent dehydration, and anastomotic complications at the stoma closure site [12][13][14][15][16][17][18] . Although protective stomas are widely used in LAR for rectal cancer, it remains unclear whether such protective stomas are useful for patients.…”
Section: Introductionmentioning
confidence: 99%